Efektivitas Metode Talaqqi dalam Meningkatkan Kualitas Bacaan Santri Tahfidz di Pondok Pesantren Modern Daarul Syuhada Kota Tebing Tinggi Sumatera Utara - Syawaluddin Syawaluddin; Mahfud Hafiz; Wakib Kurniawan (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
The purpose of this study was to determine the effectiveness of the Talaqqi method in improving the quality of reading of Tahfidz students at the Daarul Syuhada Modern Islamic Boarding School in Tebing Tinggi City, North Sumatra. By using Descriptive Qualitative Methodology. The subject is located at the Modern Daarul Syuhada Islamic Boarding School in Tebing Tinggi City. Data collection used is observation, interview, and documentation. And the results of the study are that the improvement of memorization of the Koran through the planning process, implementation using the talaqqi method, the result is that many students have improved their memorization and are in accordance with the targets set by the ustadz. The indication is that the average target is 80% of 25 students. There are supporting factors in improving memorization using this method, namely Tahsin learning always runs every day, support from parents, a comfortable place to memorize the Koran. Then as for the inhibiting factors of these activities, the lack of Tahfidz subject teachers, there is laziness in students and lack of time management.